Red Wine Astringency: Correlations Between Chemical and Sensory Features - Vega-Viveros, R; Osorio-Lira, F (Academic Press, 2022)
Thirty-seven red wines from different varieties, origins, and styles were characterized to identify the chemical parameters that better correlate with wine astringency. Principal Component Analysis showed that tannin content was the most important parameter influencing overall astringency and its sub-quality dryness, followed by polyphenolic content, color index and, to a lesser extent, pH and alcoholic degree. Given that astringency is a textural sensation caused by the interaction between salivary proteins and tannins, a comparison between two tannin precipitation assays (i.e., methylcellulose, MCP; and Harbertson-Adams assays, HA) were performed to evaluate their ability as estimators of red wine astringency. Results of the sensory correlations showed that MCP and HA have a different behavior toward intensity of astringency and dryness, mainly influenced by the tannin concentration. HA exhibited a sigmoidal behavior with a better astringency predictive performance at low and mid tannin concentration range, whilst MCP showed a linear behavior with a better performance at high tannin concentration range. © 2021 The Authors